Fortifying plant fortresses: siderophores in defense against Cercospora leaf spot disease in Vigna radiata L. - Kamath, Anushree; Sharma, Abhishek; Shukla, Arpit; Parmar, Paritosh; Patel, Dhara (Frontiers in Microbiology, 2025)
Siderophores, specialized iron-chelating molecules produced by Bacillus amyloliquefaciens D5, were investigated for their role in enhancing plant defense mechanisms against Cercospora canescens in mung bean (Vigna radiata L.). Siderophores were extracted and purified using Amberlite XAD-4 and applied to plants at concentrations of 5, 10, and 15 µg/mL, followed by pathogen inoculation. The treatments significantly influenced enzymatic activities and defense-related gene expression. On Day 6, peroxidase (POD) activity reached its highest value of 0.563 in the SP15 (siderophore + pathogen at 15 µg/mL) treatment, with S15 (siderophore-only at 15 µg/mL) showing a lower but significant increase of 0.453, while control groups remained unchanged. Polyphenol oxidase (PPO) activity peaked in SP15 (0.10 U/mL), followed by S15 (0.08 U/mL), highlighting the role of these treatments in enhancing stress responses. Chitinase activity was significantly elevated in SP15 on Day 6, with a sustained response through Day 8, while no significant change was observed in the control group. Total phenolic content was highest in SP15 (100 µg/mL), showing a a ramified immune response whereas S15 recorded 80 µg/mL, significantly above the control. Gene expression analysis further demonstrated the effectiveness of siderophore and siderophore + pathogen treatments. Catalase expression was upregulated by 21.1-fold in siderophore-only treatment and amplified to 25.9-fold in SP15. Epoxide hydrolase (EH) gene expression increased by 77.3-fold in S15 and further synergized to over 90-fold in SP15. Similarly, PR10 expression showed moderate upregulation in S15 and significantly higher levels in SP15, reflecting enhanced pathogen defense. Calmodulin (CAL) gene expression was moderately regulated in S15 but significantly amplified in SP15. These findings underscore the dual role of siderophores in nutrient acquisition and as potent elicitors of plant defenses, highlighting their potential as bio-stimulants. Field trials are essential to validate these results under natural conditions and optimize their use in agriculture.